2019
DOI: 10.24059/olj.v23i3.1564
|View full text |Cite
|
Sign up to set email alerts
|

Research Ethics of Twitter for MOOCs

Abstract: This study examined the ethical considerations researchers have made when investigating MOOC learners' and teachers' Twitter activity. In so doing, it sought to addresses the lack of an evidencebased understanding of the ethical implications of research into Twitter as a site of teaching and learning. Through an analysis of 31 studies, we present a mapping of the ethical practices of researchers in this area. We identified potential ethical issues and concerns that have arisen. Our main contribution is to seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…This study found that approximately 80% of the papers reviewed did not address issues related to ethics and data collection. This finding is consistent with those reported by Costello, Donlon and Brown (2019). The requirements of ethical approval for the use of Twitter data for research remains inconsistent among researchers.…”
Section: Ethicssupporting
confidence: 90%
See 2 more Smart Citations
“…This study found that approximately 80% of the papers reviewed did not address issues related to ethics and data collection. This finding is consistent with those reported by Costello, Donlon and Brown (2019). The requirements of ethical approval for the use of Twitter data for research remains inconsistent among researchers.…”
Section: Ethicssupporting
confidence: 90%
“…However, Twitter users may not be aware of the way researchers can use their data and express the concern that researchers should not use their data without informed consent (Fiesler & Proferes, 2018). In many instances, researchers themselves do not pay attention to the requirement of ethics or treat data from Twitter as part of the public domain (Costello, Donlon & Brown, 2019). This apparent indifference creates a dilemma for researchers, ethics boards and IRBs, and users.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maxim, "if you are not paying you are the product," may be relevant (Hirsch, 2013). Ethical norms for students taking multi-year programs and paying large fees may seem less relevant with more casual learners in MOOCs (Costello et al, 2019). Studies of attitudes to consent, and the benefits they feel may accrue from allowing their data to be used, indicate that students have concerns about privacy and surveillance but in large part they place trust in their university to use their data ethically and appropriately (Slade et al, 2019;Tsai et al, 2021).…”
Section: Review Of the Literaturementioning
confidence: 99%